2021
DOI: 10.1108/meq-11-2020-0268
|View full text |Cite
|
Sign up to set email alerts
|

The impact of individual motivation on employee voluntary pro-environmental behaviours: the motivation towards the environment of Polish employees

Abstract: PurposeEnvironmental management researchers stress the need to study the determinants of employee pro-environmental behaviour in different cultural settings. This study focusses on employee voluntary pro-environmental behaviours in Poland. It aims (1) to examine the scope of employee green behaviours in the private and public sphere and (2) to explore the relationship between individual motivation and pro-environmental behaviours.Design/methodology/approachSelf-administered questionnaire was used for collectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
0
13
0
2
Order By: Relevance
“…voluntary vs discretionary or low intensity vs high intensity). Based on the approaches in consumer behavior and directions from human resources management (Budzanowska-Drzewiecka and Tutko, 2021; Kim et al , 2016; Lee et al , 2014), this study found that frontline employees’ green idea activist behavior was significantly influenced by other types of pro-environmental behaviors, such as green idea generation behavior and green idea promotion behavior, instead of by other psychological and attitudinal variables.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…voluntary vs discretionary or low intensity vs high intensity). Based on the approaches in consumer behavior and directions from human resources management (Budzanowska-Drzewiecka and Tutko, 2021; Kim et al , 2016; Lee et al , 2014), this study found that frontline employees’ green idea activist behavior was significantly influenced by other types of pro-environmental behaviors, such as green idea generation behavior and green idea promotion behavior, instead of by other psychological and attitudinal variables.…”
Section: Discussionmentioning
confidence: 94%
“…From a theoretical perspective, compared to prior research focusing on the unidimensionality of employees’ pro-environmental behaviors (Kim et al , 2016), this study considers the different aspects of employees’ pro-environmental behaviors and examines the antecedents of environmental activist behavior, helping hospitality enterprises to make their green initiatives and practices more effective and efficient. Budzanowska-Drzewiecka and Tutko (2021) argued that it is challenging to predict all types of employees’ pro-environmental behaviors with the same psychological and organizational factors because they require different effort and involvement in activities at work (e.g. voluntary vs discretionary or low intensity vs high intensity).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have begun investigating the pro-environmental behaviors (PEBs) of employees. Researchers have investigated the influence of employees' knowledge/awareness on the environment, ecological worldviews, attitudes and behaviors (Budzanowska-Drzewiecka and Tutko, 2021; Tamar et al , 2021). Researchers proposed that it could be necessary to analyze motivational determinants, environmental intentions and environmental behavior that may occur between variables (Loureiro et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bu sayede özerk motivasyon ve kontrollü motivasyon şeklinde iki alt kategori oluşturulmuştur (Hicklenton vd., 2019: 2). Çevreci davranışların ÇKMÖ kullanılarak araştırıldığı çeşitli çalışmalarda, ÇKMÖ'nin alt ölçeklerinin özerk motivasyon ve kontrollü motivasyon gruplamasına bağlı kalınarak iki temel alt grupta ele alınarak uygulandığı gözlemlenmiştir (Hicklenton vd., 2019;Budzanowska-Drzewiecka ve Tutko, 2021;Lavergne vd., 2010). ÖBT'ne göre sınıflandırılmış motivasyon alt türlerini temel alan ÇKMÖ'nin kullanıldığı bu çalışmada ise ölçek 6 alt boyutta ele alınmıştır.…”
Section: çEvreye Karşı Motivasyonunclassified
“…Çevreci davranışlar için kişilerin motivasyonunu tespit etmeye hizmet eden çevreye karşı motivasyon kavramı, literatürde ulusal ve uluslar arası çeşitli araştırmaların konusu olmuştur. Yapılan çalışmalarda; çevreci davranışlar ve motivasyon ilişkisi (Pelletier vd., 1998;Green-Demers vd., 1997;Aitken vd., 2016;Villacorta vd., 2003), çevreci davranışlar için motivasyon eksikliği (Pelletier vd., 1999), çalışanların çevreci davranışları üzerinde motivasyonun etkisi (Budzanowska-Drzewiecka ve Tutko, 2021;Graves vd., 2013;Hicklenton vd., 2019;Graves ve Sarkis, 2018;Graves vd., 2019), adolesanların çevreye karşı motivasyonları (Renaud-Dube vd., 2010;Boeve-de Pauw ve Van Petegem, 2017;Sass vd., 2018), hükümetin çevresel düzenlemelere ilişkin yaklaşımlarının kişilerin çevreye karşı motivasyonlarına etkisi (Lavergne vd., 2010), Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi, Yıl: 2022 Cilt: 25 Sayı: 25. Yıl Özel Sayısı okul öncesi öğretmen adaylarının çevreye karşı motivasyonları (Yazıcı vd., 2013;Özkubat ve Demiriz, 2013) ve çevreci etkinlikler yoluyla fen bilgisi öğretmen adaylarının çevreye karşı motivasyonlarının geliştirilmesi (Karaarslan vd., 2014) gibi konularda çeşitli araştırmalar yürütülmüştür.…”
Section: Introductionunclassified